A Systematic Curriculum Design Study in Maritime Vocational Education (Marketing and Innovation Integration in Maritime Management Curricula) - Larsen Barasa; Tri Cahyadi; Marihot Simanjuntak (International Journal of Educational Practice and Policy, 2026)
The maritime management sector increasingly demands graduates equipped with marketing acumen and innovation capacity alongside traditional operational competencies, yet maritime vocational curricula have been slow to integrate these dimensions systematically. This study investigates how systematic curriculum design can facilitate the integration of marketing and innovation competencies into maritime management programs within Indonesian maritime vocational education. Employing a qualitative research design, data were gathered through semi-structured interviews with 12 curriculum and maritime industry experts, 18 maritime management lecturers, and 15 recent graduates across three maritime polytechnic institutions. Analytical procedures combined thematic analysis, cross-group comparison, and narrative synthesis. The findings reveal five curricular dimensions requiring systematic integration: industry-responsive competency mapping, innovation-oriented pedagogical design, marketing knowledge embedding within operational modules, experiential industry-linked learning architecture, and outcome-based assessment alignment. Cross-group analysis demonstrated that experts emphasized strategic market positioning of maritime services, lecturers identified structural rigidity as a primary barrier to innovation integration, and graduates reported a disconnect between curricular content and the commercial realities of contemporary maritime management. The study contributes a systematic curriculum design framework grounded in the triple helix model and ADDIE methodology, positioning marketing and innovation not as supplementary electives but as structurally integrated dimensions of maritime management professional competence. Each framework component is explicitly derived from a corresponding empirical theme through a step-by-step mapping process, ensuring methodological transparency and design credibility.